Argumentative Scales and Relations in the ProphetMuhammad’s ص( (Hadith A Pragmatics Approach - harrar, Nassim; .saadelli, salim (The Notebooks of the Algerian Poetics Laboratory Journal, 2025)
The subject of our study seeks to clarify the types of pilgrimage ladders in the appeal of Zabrqan bin Badr and Amr bin Al-Ahtham to the Messenger of Allah صلى الله عليه وسلم. It also reveals the various pilgrimage relations between the needy, in analysis and application, with the aim of revealing the connotations of the saying and their effectiveness among the speakers, discovering the complementary relationship between the pilgrim ladders and the various pilgrim relations,and clarifying their role in understanding the meaning and analysis of the discourse. It also seeks to highlight the methodological perceptions presented by these concepts to analyze the texts and understand the mechanisms of persuasion.